(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Medical imaging allows scientist and physicians to decide about life saving information regard to the human physiological activities. It plays an important role in the diagnosis, therapy and treatment of various organs, tumors and other abnormalities. There are more than 120 types of brain tumors Brain tumors contain all tumors inside the cranium or in the central spinal canal. They are produced by an abnormal and uncontrolled cell division, normally either in the brain itself (neurons, glial cells (astrocytes, oligodendrocytes, ependymal cells, myelin-producing Schwann cells), lymphatic tissue, blood vessels), in the cranial nerves, in the brain envelopes (meninges), skull, pituitary and pineal gland, or spread from cancers primarily located in other organs (metastatic tumors). Any brain tumor is naturally serious and dangerous because of its invasive and infiltrative character in the limited space of the intracranial cavity